2021
DOI: 10.1182/bloodadvances.2020002998
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma cell populations with distinct oncogenic programs release podoplanin as procoagulant extracellular vesicles

Abstract: Vascular anomalies, including local and peripheral thrombosis, are a hallmark of glioblastoma (GBM) and an aftermath of deregulation of the cancer cell genome and epigenome. Although the molecular effectors of these changes are poorly understood, the upregulation of podoplanin (PDPN) by cancer cells has recently been linked to an increased risk for venous thromboembolism (VTE) in GBM patients. Therefore, regulation of this platelet-activating protein by transforming events in cancer cells is of considerable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 46 publications
(82 reference statements)
2
63
0
2
Order By: Relevance
“…These interactions can have direct consequences on blood homeostasis. For instance, several reports show that tumor EVs transport pro‐coagulant factors such as tissue factor, PSGL‐1, or podoplanin and promote thrombosis through interactions with platelets or with neutrophils 94–97 . The pro‐thrombotic activity of tumor EVs appears to vary depending on the subtype of EV and the stage of the secreting tumor cell 96,98 .…”
Section: Interaction With Blood Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions can have direct consequences on blood homeostasis. For instance, several reports show that tumor EVs transport pro‐coagulant factors such as tissue factor, PSGL‐1, or podoplanin and promote thrombosis through interactions with platelets or with neutrophils 94–97 . The pro‐thrombotic activity of tumor EVs appears to vary depending on the subtype of EV and the stage of the secreting tumor cell 96,98 .…”
Section: Interaction With Blood Componentsmentioning
confidence: 99%
“…For instance, several reports show that tumor EVs transport pro‐coagulant factors such as tissue factor, PSGL‐1, or podoplanin and promote thrombosis through interactions with platelets or with neutrophils. 94 , 95 , 96 , 97 The pro‐thrombotic activity of tumor EVs appears to vary depending on the subtype of EV and the stage of the secreting tumor cell. 96 , 98 While platelet aggregation correlates with PMN formation, 99 the role of tumor EVs in this process has not yet been investigated.…”
Section: Interaction With Blood Componentsmentioning
confidence: 99%
“…It was reported that exosome-like EVs shed from glioma cells in vitro and vivo. Injection of glioma-derived podoplanin carrying extracellular vesicles activates platelets, while tissue factor carrying extracellular vesicles activate the clotting cascade [45].In addition, BDEVs have been reported to be involved in the pathophysiological processes of stroke and TBI [13,17], but their role in sepsis remains unknown. In our study, we found that BDEVs injection induced systemic coagulation activation and that BDEVs from septic rats exacerbated this process.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic approaches allow researchers to understand protein signatures of native and engineered EVs ( Nasiri Kenari et al, 2019 ; van Balkom et al, 2019 ), which may have implications in quality control platforms to confirm the identity and test for purity of therapeutic EVs. Proteomics has been used to assess plasma EVs after separation from lipoproteins (i.e., lipoprotein particle depletion) ( Karimi et al, 2018 ), tissue-derived stress/damage markers following cardiac-EV isolation ( Claridge et al, 2021 ), and oncogenic mutations on EV proteome landscape ( Al-Nedawi et al, 2008 ; Lobb et al, 2017 ; Emmanouilidi et al, 2019 ; Chennakrishnaiah et al, 2020 ; Shafiq et al, 2021 ; Tawil et al, 2021 ). Several key omic-based studies have provided direct insight into the composition and (re)classification of EVs, their biogenesis and content ( Greening et al, 2015 ; Kowal et al, 2016 ; Jeppesen et al, 2019 ; Kugeratski et al, 2021 ; Martinez-Greene et al, 2021 ; Rai et al, 2021 ).…”
Section: Challenges To Further Development Of Ev Therapiesmentioning
confidence: 99%